The Role of Influencers in Shaping Consumer Interest in Purchasing Online Shop Products (Case Study of Binjai District, Langkat Regency) - Siti Nurhaliza; Raja Sakti Putra Harahap (Journal of Economics and Business (JECOMBI), 2025)
This study aims to understand the role of influencers in shaping consumer interest in purchasing products from on line shops in Binjai District , Langkat Regency. Along with the development of technology and social media, influencers have become an essential elements in marketing strategies . This research uses a qualitative method with in- depth interviews conducted with two influencers , several on line sellers , and consumers . The results show that influencers play a significant role in building trust , educate , and inspiring their audience . The success of promotions heavily depends on the quality of content created by influencers and their interactions with the audience . It is recommended for companies and brands to choose influencers who have credibility and an audience that align with the promoted products , and for influencers to maintain an authentic relationship with their followers to make the promotion more effective.